IMPACT OF SOCIOECONOMIC FACTORS ON NUTRITIONAL STATUS IN PRIMARY SCHOOL CHILDREN - Babar, Nabeela Fazal; Muzaffar, Rizwana; Khan, Muhammad Athar; Imdad, Seema (Journal of Ayub Medical College Abbottabad, 2010)
Background: Child malnutrition is a major public health and development concern in most of the poor communities leading to high morbidity and mortality. Various studies have highlighted the factors involved. The present study focuses on socioeconomic inequality resulting in malnutrition. Objectives of the Study were to find the Impact of socio-economic factors on nutritional status in primary school children. Methods: It was a cross sectional survey conducted at Lahore from February to August 2005 among primary schools from public and private sectors to assess the nutritional status of primary school going children age 5-11 years belonging to different socio economic classes of the society. Systematic random sampling technique was applied to collect the sample. Body Mass Index in relation to NHANES reference population was used for assessing nutritional status. Results: The nutritional status of children from lower socio economic class was poor as compared to their counter parts in upper socio economic class. Children with BMI <5thpercentile were 41% in lower class while in upper class it was 19.28%. Prevalence of malnutrition was 42.3% among children of illiterate mothers as compare to 20% in those of literate mothers. Conclusion: Poverty, low literacy rate, large families, food insecurity, food safety, women’s education appears to be the important underlying factors responsible for poor health status of children from low socioeconomic class. It requires economic, political and social changes as well as changes for personal advancement mainly through educational opportunities to improve the nutritional status of the children. Keywords: Body Mass Index, BMI, Malnutrition, Nutrition, Children, Primary School